A Retrospective Observational Study Using Administrative Databases to Assess the Risk of Spontaneous Abortions Related to Environmental and Socioeconomic Conditions - Massimo Giotta; Nicola Bartolomeo; Paolo Trerotoli (Life, 2023)
Miscarriage is one of the most frequent adverse events that occurs during pregnancy. This retrospective study aimed to verify if the environmental and socioeconomic conditions related to geographical areas where women live, and the socio-demographic and clinical factors play a role in the risk of spontaneous abortion (SA). The analyses were conducted by hospital discharge records (HDRs) from public and private hospitals in Apulia from 1 January 2021 to 31 December 2021. Women with an age over 40 years old had a major risk of SA compared with women under 18 years (OR 2.30, IC95%1.16–4.54). A reduction in the risk of SA was found for women with an endocrinological or metabolic disease (OR 0.28, 95% CI 0.19–0.41), while genetic disease greatly increases the risk (OR 9.63, IC95% 1.98–46.86). The greatest risk of spontaneous abortion was found in the province of Taranto compared to the province of Foggia (OR 2.01, 95% CI 1.52–2.64). The provinces with a higher risk of SA in the multiple comparisons were Taranto, Brindisi, and BAT. Municipalities with socioeconomic disadvantages classified as very low, low, and medium had a higher risk of SA compared to the municipalities with a high disadvantage. In conclusion, our study indicates the possible association between SA rate and environmental conditions. Additionally, the socioeconomic, clinical, and demographic factors were related to the risk of SAs.